Choosing the Best House in a Bad Neighborhood: Location Strategies of Human Rights INGOs in the Non‐Western World1. Issue 1 (15th December 2014) - Barry, Colin M.; Bell, Sam R.; Clay, K. Chad; Flynn, Michael E.; Murdie, Amanda
Abstract : What determines the location of those human rights international non‐governmental organization (INGO) resources found outside of the highly developed Western democracies? We draw a distinction between the bottom‐up mobilization processes driving the location of human rights organization (HRO) members from the top‐down strategic concerns driving where HRO leaders place permanent offices . In particular, we find that, while political opportunity structures generally increase the likelihood that a state has HRO members, it has a curvilinear influence on the number of HRO secretariats, which typically locate in areas seen as having a higher need for organizational resources. Further, while there is no clear connection between human rights abuses and HRO memberships in a state, HROs' strategic concerns lead them to place offices with reference to both local and neighborhood "need"—in other words, levels of repression.